2011
DOI: 10.1021/ja111280t
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Selectivity of Charged Phenyl Radicals toward Amino Acids in a Fourier Transform Ion Cyclotron Resonance Mass Spectrometer

Abstract: The reactivity of ten charged phenyl radicals toward several amino acids was examined in the gas phase in a dual-cell Fourier-transform ion cyclotron resonance (FT-ICR) mass spectrometer. All radicals abstract a hydrogen atom from the amino acids, as expected. The most electrophilic radicals (with a greater calculated vertical electron affinity (EA) at the radical site) also react with these amino acids via NH2 abstraction (a nonradical nucleophilic addition-elimination reaction). Both the radical (hydrogen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…2(f)). The fragment peak at m/z 378 represents loss of the sugar moiety (116) followed by the neutral loss of HCl (36). This type of cleavage pattern was also observed for 2,4,6-TCP-O-dG (5) ( Fig.…”
Section: Fragmentation Pathwayssupporting
confidence: 55%
See 2 more Smart Citations
“…2(f)). The fragment peak at m/z 378 represents loss of the sugar moiety (116) followed by the neutral loss of HCl (36). This type of cleavage pattern was also observed for 2,4,6-TCP-O-dG (5) ( Fig.…”
Section: Fragmentation Pathwayssupporting
confidence: 55%
“…Our calculations also demonstrate the destabilizing influence of 2‐Cl and 4‐Cl substituents, but suggest a slightly destabilizing influence by 3‐Cl atoms (Table ). The calculations (Table ) and experimental MS experiments demonstrate that homolytic bond cleavage of the O‐linked C8‐dG nucleoside adducts is not driven by stability of the phenyl radical product. This prediction is contrasted by fragmentation of the Bn‐O‐dG derivative ( 7 ) in which benzyl radical stability is expected to provide the driving force for production of the nucleoside distonic ion.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Numerous positively charged phenyl radicals were later allowed to react with several partially isotope labeled amino acids. 281 Results obtained for partially deuterium-labeled leucine and proline indicated that only a fraction of the hydrogen atom abstractions, if any, occurred at the α-carbon of the amino acid. Instead, the majority of hydrogen atoms are abstracted from the alkyl side chain.…”
Section: Properties and Reactivitymentioning
confidence: 99%
“…Also, antioxidant enzymes such as superoxide dismutase and peroxidase, can inhibit lipid oxidation by catalyzing the conversion of superoxide anion to hydrogen peroxide and the conversion of hydrogen peroxide to water, respectively (Valko et al, 2007). Besides, the selectivity of radical attacks on amino acid side chains and physical location the radical generation can be related to the energy of oxidation (Pates et al, 2011). Finally, heating proteins in the presence of sugars can form brown polymers called melanoidins or Maillard reaction products that act as antioxidants (Žilić et al, 2012).…”
Section: Antioxidant Peptides Of White Cheese In Brinementioning
confidence: 99%